PENENTUAN NILAI SUSEPTIBILITAS DAN UKURAN PARTIKEL MAGNETIK PASIR PATAI KATA PARIAMAN SUMATERA BARAT MENGGUNAKAN METODE BALL MILLING - Annisa Alhasna Kurnia; Antonius Surbakti (Komunikasi Fisika Indonesia, 2021)
Determination of magnetic properties and magnetic particle size of sand from Kata Pariaman Beach, West Sumatera have been carried out using Pasco Magnetic Probe and scanning electron microscope (SEM) method. Sand samples that have been dried beforehand are then synthesized using two stage ball milling, namely 40 hours first stage, and second stage as a function of 10, 20, 30, and 40 hours with an iron ball with a diameter of 1.5 cm. The results showed that the value of magnetic susceptibility and mass susceptibility increases as milling time increases. The magnetic and mass susceptibility values obtained included iron oxide particles such as Magnetite Fe3O4, hematite and maghemit with a value interval of 20,000 to 110,000. The results of the x-ray fluorescence (XRF) test showed the composition of Fe and Ti increased after ball milling, while other elements such as Si decrease. The results of the study particle size by SEM had a small size with increasing ball milling time from 10, 20, 30, and 40 hours.